Interventions targeting children and young people's physical activity behavior at home: A systematic review. - Amanda L Seims; Jennifer Hall; Daniel D Bingham; Amy Creaser; Anastasia Christoforou; Sally Barber; Andy Daly-Smith (PLoS ONE)
Background and purpose Increased time at home during the COVID-19 pandemic significantly decreased children's physical activity. This systematic review aimed to evaluate the effectiveness of children's home-based physical activity interventions, and identify 'active ingredients' underpinning these. Methods Databases searched-AMED, PsychINFO, CINAHL, Cochrane, EMBASE, PubMed/Medline, Scopus, SPORTDiscus and Web of Science, from inception until June 2022. Eligibility criteria-children aged 2-16 years, targeting home-based physical activity, a control group, and physical activity measured pre- and post- intervention. Studies were excluded if it was not possible to identify change in physical activity at home. The review was written following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance. Study quality was evaluated using the quality assessment tool for quantitative studies. Study design, intervention characteristics, outcome data, behavior change theory, Behavior Change Techniques (BCTs) and process evaluation data were extracted and discussed using narrative syntheses. Results 13 studies (including 1,182 participants) from 25,967 were included. Interventions primarily involved active video games, with the addition of coaching or telehealth support (n = 5). Three of the 13 studies significantly increased children's physical activity (1 = Moderate to vigorous physical activity, 2 = total volume, P<0.05). The largest effect size (d = 3.45) was for moderate to vigorous physical activity. 29% of BCTs were identified across included interventions; the most common being adding objects to the environment. The most effective intervention scored strong for design quality, incorporated telehealth coaching, and included the most commonly coded BCTs. Variation among studies and insufficient reporting of data made a meta-analysis unfeasible. Conclusion COVID-19 emphasized the importance of the home for physical activity. Whilst effectiveness of interventions was limited, building social support and self-efficacy are mechanisms that should be explored further. The review provides recommendations to improve the design and evaluation of future interventions. Trial registration Prospero registration number: CRD42020193110.